The Effectiveness of Jigsaw Model Based on Flipped Classroom to Improve Students' Critical Thinking Ability in Islamic Religious Education Learning - Makhrus Ali; Sutarto Sutarto; R Nurhayati; Hasyim Mahmud Wantu; Miftachul Amri; Tomi Apra Santosa (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the influence of the flipped classroom-based Jigsaw model on students' critical thinking skills in PAI learning. This type of research is quantitative research with the use of meta-analysis. The inclusion criteria in this study are research published in 2021-2024; Research must be relevant; research must be experimental or quasi-experimental methods; research must be indexed by SINTA, Scopus or Web of Science; Research must be carried out on Islamic Religious Education learning and research data must be complete to calculate the effect size value. Data analysis is to calculate the effect size value with the help of a JSAP application. The results of the study concluded that the flipped classroom-based jigsaw model positively influenced the thinking ability of students in PAI learners with a score (rRE= 1.026; z= 7.086 and p < 0.001). This finding provides important information for applying the flipped classroom-based jigsaw learning model to encourage the critical thinking skills of school students.